Nitrogen Nutrition Promotes Rhizome Bud Outgrowth via Regulation of Cytokinin Biosynthesis Genes and an Oryza longistaminata Ortholog of FINE CULM 1 - Shibasaki, Kyohei; Takebayashi, Arika; Makita, Nobue; Kojima, Mikiko; Takebayashi, Yumiko; Kawai, Misato; Hachiya, Takushi; Sakakibara, Hitoshi (Frontiers in Plant Science, 2021)
Oryza longistaminata, a wild rice, can propagate vegetatively via rhizome formation and, thereby, expand its territory through horizontal growth of branched rhizomes. The structural features of rhizomes are similar to those of aerial stems; however, the physiological roles of the two organs are different. Nitrogen nutrition is presumed to be linked to the vegetative propagation activity of rhizomes, but the regulation of rhizome growth in response to nitrogen nutrition and the underlying biological processes have not been well characterized. In this study, we analyzed rhizome axillary bud growth in response to nitrogen nutrition and examined the involvement of cytokinin-mediated regulation in the promotion of bud outgrowth in O. longistaminata. Our results showed that nitrogen nutrition sufficiency promoted rhizome bud outgrowth to form secondary rhizomes. In early stages of the response to nitrogen application, glutamine accumulated rapidly, two cytokinin biosynthesis genes, IPT and CYP735A, were up-regulated with accompanying cytokinin accumulation, and expression of an ortholog of FINE CULM1, a negative regulator of axillary bud outgrowth, was severely repressed in rhizomes. These results suggest that, despite differences in physiological roles of these organs, the nitrogen-dependent outgrowth of rhizome axillary buds in O. longistaminata is regulated by a mechanism similar to that of shoot axillary buds in O. sativa. Our findings provide a clue for understanding how branched rhizome growth is regulated to enhance nutrient acquisition strategies.